Plasma growth differentiation factor 15: a novel tool to detect early changes of hereditary transthyretin amyloidosis - Okada, Masamitsu; Misumi, Yohei; Masuda, Teruaki; Takashio, Seiji; Tasaki, Masayoshi; Matsushita, Hiroaki; Ueda, Akihiko; Inoue, Yasuteru; Nomura, Toshiya; Nakajima, Makoto; Yamashita, Taro; Shinriki, Satoru; et al. (ESC Heart Failure, 2021)
Aims Hereditary transthyretin (ATTRv) amyloidosis is the most frequent and representative form of autosomal dominant hereditary systemic amyloidosis. Disease‐modifying treatments of the disease are more effective during the early stages, and we require biomarkers to detect early pathological changes for prompt diagnosis. This study aimed to investigate whether plasma growth differentiation factor 15 (GDF‐15) levels could aid detection of early pathological changes in ATTRv amyloidosis. Methods and results We retrospectively studied 32 patients with ATTRv amyloidosis, eight asymptomatic TTR mutation carriers, and eight healthy volunteers. We evaluated plasma GDF‐15 levels in these subjects as related to levels of brain natriuretic peptide and high‐sensitivity troponin T, echocardiographic features, 99mTc‐pyrophosphate (PYP) scans, and cardiac magnetic resonance imaging findings. Plasma GDF‐15 levels significantly increased even in asymptomatic TTR mutation carriers compared with healthy volunteers (P < 0.01). Plasma GDF‐15 levels were significantly correlated with plasma brain natriuretic peptide values (P < 0.01), serum high‐sensitivity troponin T values (P < 0.05), and interventricular septal thickness at end‐diastole (P < 0.01) in patients with ATTRv amyloidosis. Plasma GDF‐15 levels in patients with PYP‐positive ATTRv amyloidosis were significantly higher than those in patients with PYP‐negative ATTRv amyloidosis (P < 0.01). Plasma GDF‐15 levels in patients with late gadolinium enhancement‐positive ATTRv amyloidosis were significantly higher than those in patients with late gadolinium enhancement‐negative ATTRv amyloidosis (P < 0.01). Groups of patients with different TTR genotypes manifested different plasma GDF‐15 levels. Conclusions Growth differentiation factor 15 may reflect early pathological changes of ATTRv amyloidosis.